If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 33x + -2 = 32x + 2 Reorder the terms: -2 + 33x = 32x + 2 Reorder the terms: -2 + 33x = 2 + 32x Solving -2 + 33x = 2 + 32x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32x' to each side of the equation. -2 + 33x + -32x = 2 + 32x + -32x Combine like terms: 33x + -32x = 1x -2 + 1x = 2 + 32x + -32x Combine like terms: 32x + -32x = 0 -2 + 1x = 2 + 0 -2 + 1x = 2 Add '2' to each side of the equation. -2 + 2 + 1x = 2 + 2 Combine like terms: -2 + 2 = 0 0 + 1x = 2 + 2 1x = 2 + 2 Combine like terms: 2 + 2 = 4 1x = 4 Divide each side by '1'. x = 4 Simplifying x = 4
| n-1+2n=-4 | | 18x+7=-5FORX | | 1.2/58 | | 1.2/5.8 | | 27x-3=26x+1 | | 6x/2=33 | | 5x-5=5-5x | | 5x+2=-9 | | -20x^2+17x+24=0 | | 15x=16x-8 | | 4(x^2+5)=2(x^2+1) | | 18-1/2=6 | | 3*1/8= | | 18x+9=19x+2 | | 3xsquared=9 | | 4(3x+2y)-7x-5(2y-4)= | | 224/32= | | 3(-4m-6)=-6(m+3) | | 30*93= | | -38-7k=-8(k+4) | | 32/224 | | -2x-1=-9x-x | | 5/9=1/4x | | 25*79= | | 26x=27x-5 | | 2y^3+3y^2=0 | | 5x+10y=-2 | | 157=-192+h | | 11*38= | | -2z/2 | | 4f-9-3f+10= | | -18=-15-3(6t+5) |